2018
DOI: 10.1159/000491018
|View full text |Cite
|
Sign up to set email alerts
|

Stress Aggravates High-Fat-Diet-Induced Insulin Resistance via a Mechanism That Involves the Amygdala and Is Associated with Changes in Neuroplasticity

Abstract: Background: The notion that exposure to chronic stress predisposes individuals to developing type 2 diabetes (T2D) has gained much attention in recent decades. Long-term stress induces neuroadaptation in the amygdala and increases corticosterone levels. Corticosterone, the major stress hormone in rodents, induces insulin resistance and obesity in mice. However, little is known about whether the stress-induced amygdalar neuroadaptation could promote the risk of T2D. Methods: We used an 11-week high-fat diet (HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Chronic stress induces a sustained increase in the activity of PVH CRH neurons [41], which may mimic the effect induced by NachBac in clamping the neuron activity at high levels. Thus, disrupted neuron responsiveness may explain obesity development induced by chronic stressors (e.g., social stress) [42,43] and synergistic effects between chronic stress and HFD on obesity development [6][7][8][9]. Given the socioeconomic stress faced by humans is chronic in nature, and a positive correlation between cort levels and low socioeconomic status [44], our results support that chronic stress contributes significantly to obesity development, especially in the current HFD environment.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Chronic stress induces a sustained increase in the activity of PVH CRH neurons [41], which may mimic the effect induced by NachBac in clamping the neuron activity at high levels. Thus, disrupted neuron responsiveness may explain obesity development induced by chronic stressors (e.g., social stress) [42,43] and synergistic effects between chronic stress and HFD on obesity development [6][7][8][9]. Given the socioeconomic stress faced by humans is chronic in nature, and a positive correlation between cort levels and low socioeconomic status [44], our results support that chronic stress contributes significantly to obesity development, especially in the current HFD environment.…”
Section: Resultssupporting
confidence: 65%
“…Specifically, HFD feeding is associated with disrupted diurnal rhythms in feeding and metabolism, and time-scheduled feeding alleviates the obesity and associated metabolic syndromes by HFD [5], suggesting an important contribution of disrupted diurnal rhythms to diet-induced obesity (DIO). Recent studies have also suggested a potential role for stress in worsening DIO [6][7][8][9]. Despite intense research, the cellular mechanism in the brain underlying HFD feeding and its potential interaction with stress in obesity development remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Animals that received saline served as the control group (vehicle). Blood samples were collected at 3 h from the retro-orbital sinuses of anesthetized mice using a heparinized capillary tube (Tsai et al, 2018 ). Alternatively, under anesthesia, blood samples were collected at 6 h via cardiac puncture using a 26G needle rinsed with 10 μl of heparin (5,000 IU/ml; Leo Pharmaceutical, Ltd., Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Animals that received saline served as the control group (vehicle). Blood samples were collected at 3 h from the retro-orbital sinuses of anesthetized mice using a heparinized capillary tube 29 . Alternatively, under anesthesia, blood samples were collected at 6 h via cardiac puncture using a 26G needle rinsed with 10 ml of heparin (5000 IU/mL; Leo Pharmaceutical, Ltd., Denmark).…”
Section: Peripheral Injection Of Lps and Tfpmentioning
confidence: 99%